Knowledge, health-related behaviour, and attitudes towards obesity among adult with obese and non-obese/ Athirah Hanum Mohd Zabia and Chua Siew Kuan - Mohd Zabia, Athirah Hanum; Chua, Siew Kuan (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
A multidisciplinary approach by assessing the obesity risk knowledge (ORK), health-related behaviors (HRB) and attitudes towards obese people (ATOP), specifically using the knowledge, attitudes and practices (KAP) model is essential to specify potential candidates for obesity reduction strategies. This study aimed to examine the difference of ORK, ATOP and HRB and its association between these three variables among adults with obese and non-obese. 148 forty-eight participants ages 23.20 (2.96) years were enrolled in this cross-sectional study. A self-administered questionnaire was used to collect information on sociodemographic, characteristics and KAP of the respondent on obesity. The anthropometric data (height and weight) were taken. The differences between groups in variables were analysed using independent t-test and the Spearman rank coefficient correlation for the relationships of variables. A quarter of participants were obese (27.7%). There was significant (p < 0.01) higher in HRB score among obese adult compared to non-obese with (59.56 ± 6.09 and 55.90 ± 5.81, respectively). A weak negative correlation was found between the ATOP score and HRB score of non-obese adult (rs= -0.25, p = 0.01). Obese people could have better effort in implementing good health-related behaviours towards obesity compare to those who was non-obese. Hence, the effort on combating obesity should be to target all levels of body type despite the targeted obese people. The health care institutions and health sciences students should cooperate in dealing this obesity issues as both may contribute a huge impact towards the effectiveness in managing this issue.